Hakikat dan Fungsi Sains dalam Membangun Pendidikan di Abad 21 - Ramdhani, Ahmad Fauzi; Zaqiyah, Nuraini; Hamid, Alya Lathifa; Anisa, Mutiara; Ernasari, Ernasari; Mahardika, I Ketut; Handono, Sri (Jurnal Ilmiah Wahana Pendidikan, 2024)
In this era of globalization, science and technology have become an integral part of human life. There are interpreation and interdependency between science, technology and society. Almost all aspects of adult human life are surrounded by problems containing scientific implications. Therefore, the literacy and technological literacy) for all citizens have become a vulnerable demands so that we are able to utilize science and technology for humanity, able to make decisions based on scientific concepts, and are able to search and use scientific information in solving problems faced in everyday life. The negative effects of developments of icteks and globalization are significantly in all parts of the world, including in Indonesia. There has been a degradation of characters such as 1) reduced sense of responsibility, 2) reduced respect, 3) Increased victims, 4) reduced discipline, 5) slump of work ethic, 6) degenerate ethics, 7) reduced manners, 8) thundering the sense of concern and so on. To solve the problem, it is necessary to seek the science education model that can lead to students to become citizens that are literacy of science and technology and character. One of the science learning models that are able to contribute to the formation of the insances of science and technology literacy and are able to grow developing the character of the students is the learning model of the science-technology-society. Research Research Sadia, et al. (2014) shows that the application of STM learning model is effective in developing the character of students who includes discipline, honesty, creativity, hard work, curiosity, communicative, concern, and responsibility.